Intracytoplasmic Sperm Injection Cycle Outcomes in Women Aged 40 Years and Over - Oya Aldemir; Runa Ozelci; Serdar Dilbaz; Berna Dilbaz; Emre Baser; Yaprak Ustun (Gynecology Obstetrics & Reproductive Medicine)
Objective: The main detrimental factor in female fertility is maternal age. Clinical pregnancy and live birth rates decline gradually with age and this decline is dramatical over 40 years. In this study, we examined the in vitro fertilization/intracytoplasmic sperm injection cycle outcomes of women aged 40 years and over.